Kesesuaian lahan budi daya rumput laut Caulerpa sp. di Perairan Tanjung Kamala, Minahasa Utara - Mamonto, Reva E.; Ngangi, Edwin. L. A.; Undap, Suzanne L.; Kreckhoff, Reni L.; Longdong, Sammy N. J.; Monijung, Revol J.; Pangemanan, Novie P. L. (e-Journal BUDIDAYA PERAIRAN, 2024)
Abstract Bahoi Waters is located in West Likupang District, known as a coastal village that has a lot of fishing and marine potential. Utilization of Bahoi waters for seaweed cultivation requires good seawater quality to meet the requirements for cultivation. Water quality is one of the factors that plays an important role in the success of seaweed cultivation. The aim of the research was to determine the suitability of water in Bahoi Village for  land for seaweed (Caulerpa sp.) cultivation. The research used in situ measurements at 3 stations, namely: Station A (Existing Cultivation Location), Station B (Tanjung Kamala Waters), and Station C (Tamperong Island Waters). Data collection was carried out 2 times with 3 repetitions for measurement of water parameters. Measurement time was carried out at 07:00 – 09:00; 12:00-14:00, and 17:00- 19:00. Data was analyzed by comparing physical parameters and chemical parameters at each station with a scoring table and weights in the land suitability matrix. The conformity class determination obtained was: Very Suitable with a value range of 37 – 48 (S1), Suitable 25 – 36 (S2), and Not Suitable 16 – 24 (S3). The scoring value for suitability of water quality parameters at Station A was 46, Station B 47, and Station C 44. In conclusion, all stations are in the Very Suitable class for cultivating Caulerpa sp.  Keywords: Caulerpa sp., water quality, seaweed